A new species of Moina Baird, 1850 (Cladocera: Moinidae) from Thailand - Alonso, Miguel; Neretina, Anna N.; Sanoamuang, La-Orsri; Saengphan, Nukul; Kotov, Alexey A. (Zootaxa, 2019)
A new species of Moina Baird, 1850 (Cladocera: Moinidae) is described based on material collected from Thailand (South-East Asia). In tropical Asia, Moina siamensis sp. nov. could be confused easily with M. weismanni Ishikawa, 1896, because of morphological similarities in parthenogenetic females and males of both species. The outstanding difference between these two taxa concerns the structure of the ephippium in gamogenetic females, which is highly visible under light and scanning electron microscopes. The mature ephippium of M. weismanni is strongly tuberous, with distinct borders between cells, whereas the ephippium of M. siamensis sp. nov. is significantly less tuberous, with prominent longitudinal lines in its central region. Since gamogenetic females only appear sporadically in moinid populations, distribution ranges of M. siamensis sp. nov., M. weismanni and sibling taxa must be clarified precisely using genetic markers in the future. Preliminary investigations of the ephippium structure may be useful for estimating the differences between populations, thus revealing much diversity within Moinidae.